2017
DOI: 10.4172/2165-7920.1000924
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Pregnancy Complicated with Type 1 Hereditary Angioedema (HAE 1)

Abstract: Hereditary angioedema (HAE) is an inherited autosomal dominant trait and symptoms of HAE include sudden onset of edema in various organs, such as subcutaneous edema, laryngeal edema and gastrointestinal tracts mucosa. We have experienced a case of a pregnant woman diagnosed with HAE and successfully managed her pregnancy. The patient was 37 years old, gravida 1, primiparous. She had experienced two attacks of angioedema during pregnancy but her delivery course was not affected by her HAE. The frequency of atta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…[3][4][5] Some studies have demonstrated increase in the attack rates with the subsequent pregnancies. 6,7 Different effects of HAE on pregnancy and postpartum period have been noted. Some patients have flare-ups while some experience improvement of symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] Some studies have demonstrated increase in the attack rates with the subsequent pregnancies. 6,7 Different effects of HAE on pregnancy and postpartum period have been noted. Some patients have flare-ups while some experience improvement of symptoms.…”
Section: Introductionmentioning
confidence: 99%